Cultural Sentience in Selected Short Stories in English: Exploring the Depths of Indian Culture through Selected Short Stories in English (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Staying true to the essence of the beliefs and practices that form a given culture that an individual conforms to, a culture is normally ingrained and dictated through stories for posterity so that an understanding of the ways, mores, customs, traditions and value system is gained in an implicit way. The influence of stories lies in the way they are told, and the effect they have on their receivers. This paper aims to study the concept of culture in the context of Indian socio-historical locale more than just the jeu d’esprit, since it intends to examine the influence of culture as depicted in Indian English literature, mainly the genre of literary short story writing. In order to restrict my topic, three short stories written by Indian writers in English shall be observed. Yet these stories do not cover the socio-cultural matrix of India in entirety, they still make an all-inclusive evaluation of the cultural link, divergence, profanation and intolerance faced by the people living in various parts and communities of the country. The stories by Rabindranath Tagore, Chaganti Somayajulu and Vishwapriya L. Iyengar have been selected for the reason that it is believed that India is a country with great diversity, deviating customs and beliefs and all these writers give a comprehensive picture of Indian culture and society. Rabindranath Tagore gives a fleeting glimpse of the Bengal of his time and Chaganti Somayajulu speaks of the South. Although my selection of writers is comprised of the most famous and even the lesser-known writers, the approach is interdisciplinary and to attain a sharper focus the short story penned by a female author Vishwapriya L. Iyengar has also been included as she truly mirrors the cultural discrimination amongst the Muslim community in India. This paper is an endeavour to provide a corroborative evidence to the concept of culture that finds unsurpassable manifestation in Indian literature in English through its numerous nuances.